Excavation, expression, and functional analysis of a novel zearalenone-degrading enzyme - Gao, Huihui; Lu, Dan; Xing, Mingyan; Xu, Qing; Xue, Feng (Folia microbiologica, 2022)
Zearalenone (ZEN) is a toxic secondary metabolite of Fusarium sp. commonly found in wheat, corn, and other crops. In addition to economic losses, ZEN can seriously endanger the health of both humans and livestock, thus presenting an urgent need for ZEN-detoxifying enzymes that function in the extreme heat or pH conditions of industrial fermenters. Here, we identify and characterize the activity of the ZEN-degrading enzyme from Exophiala spinifera, ZHD_LD, which shares 60.15% amino acid identity and a conserved catalytic triad with the well-characterized ZEN-detoxifying protein ZHD101 from Clonostachys rosea. Biochemical activity and stability assays indicated that purified recombinant ZHD_LD exhibited high activity against ZEN with optimal reaction conditions of 50 °C and pH 7.0-10.0. Structural modeling of the ZHD_LD active site and comparison with ZHD101 revealed its likely mechanism of ZEN degradation. This research provides an industrially valuable candidate enzyme for ZEN detoxification in food and livestock feed.
Keywords: Zearalenone; Fusarium; Triticum; lidé; hydrolasy; pšenice; zearalenon; Hydrolases; Humans